HUBUNGAN TINGKAT PENGETAHUAN DAN SIKAP REMAJA PUTRI TENTANG DISMENOREA DAN TINDAKAN DALAM PENANGANAN DISMENOREA DI SMP SWASTA KUALUH KABUPATEN LABUHAN BATU UTARA TAHUN 2015 - Yulia S Sitorus; Sri Rahayu Sanusi; Maya Fitria (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2016)
Dysmenorrhea is pain in the abdomen and pelvic area experienced by women as a result of her menstrual period. Dysmenorrhoea is one of the most common gynecological problems experienced by women of all ages. The incidence of dysmenorrhoea in the world is very large, approximately 50% of all women in the world suffer from dysmenorrhoea. This study aims to determine the correlation between knowledge and attitudes of young women with the action in the treatment of dysmenorrhoea in Junior High School Kualuh district Labuhan Batu Utara 2015.   This type of research is a survey by using explanatory research approach. The population in the study were all students who had as many as 53 people dysmenorrhoea class I, II, III, and made the total sample. Data was obtained through interviews using a questionnaire and analyzed by chi-square test.   From the results of the chi-square test (α <0.05), indicating there is a significant relationship between knowledge and action in the treatment of dysmenorrhoea (p = 0.005). And test results showed no relationship between attitude and action in the treatment of dysmenorrhoea (p = 0.045).   Expected that the students are always looking for health information, especially in the treatment of dysmenorrhoea through electronic media, textbooks on reproductive health, especially the health of adolescents in a school environment. And to the school in order to involve students in a health seminar activities.   Keywords: Knowledge, Attitude, Dysmenorrhea